A Forensic Analysis of Intracranial Hemorrhages in Medico-Legal Autopsies - Noreen Farid, Rabia Khan, Anwar Ali, Ghulam Muhayudin, Shahida Naveed, Faqir Ullah, Ijaz Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To analyze the prevalence, types, and causes of intracranial hemorrhages in medico-legal autopsies, highlighting the association with traumatic and non-traumatic deaths. Study Design: A retrospective study. Place and Duration: The study was conducted at Turbat Teaching Hospital, Balochistan from April 2022 to March 2023. Materials and Methods: A total of 118 patients were enrolled in the study. Patient demographics (age, sex, mode of death) were recorded, and written consent was obtained where necessary. Histopathology was performed on tissue specimens from all patients. Blood samples were analyzed for alcohol and toxicology tests. All cases underwent X-ray imaging, and full autopsies were performed. Decomposed bodies were excluded from the study. Results: The mean age of patients was 34.23 ± 18.12 years, with a body mass index (BMI) of 23.49 ± 16.78. Intracranial lesions were responsible for 13.75% of total deaths. The most common age group affected was 25–45 years, with males predominantly affected. Traumatic deaths (primarily from RTAs) were more common than non-traumatic deaths. Subarachnoid hemorrhage was the most frequent finding in autopsy. Conclusion: Intracranial hemorrhages, though a minor cause of death, often co-occur with other traumatic injuries and play a significant role in medicolegal investigations. Delayed complications like pneumonia were common in cases with prolonged hospitalization. Keywords: Intracranial hemorrhage, forensic autopsy, road traffic accidents, subarachnoid hemorrhage, medico-legal death investigation.